Sacred to profane : writings on performance and worship - Katyal, Anjum (London ; New York : Seagull Books, 2007)
With reference to India.
Includes bibliographical references.
Keywords: Theater and society -- India; Theater -- Religious aspects; Public worship -- India; Performance -- Religious aspects; India -- Religion